Highlights (Mandaluyong City, 2009)
Contents: Climate change in Southeast Asia: why it matters; Climate change mitigation to contribute to a global solution; Way forward...
Keywords: Environmental economics,Kinh tế môi trường; Southeast Asia,Đông Nam Á